Why pandemic coronavirus (SARS-CoV-2) hit different age groups of people in Southeast Asia? a case study in Bangladesh (Journal of Ideas in Health, 2022)
The new catastrophe of a novel coronavirus (COVID-19s) with unstable symptoms has rapidly pulled danger to all age groups worldwide. We investigate possible causes of the different nature and demography of COVID-19. We collected and used secondary data from the IEDCR website and “Worldometer” from 1st April to 24th June for the statistical analyses, including multi-criteria decision-making method (MCDM), topsis, advanced topsis, simple additive weighting (SAW) and weighting product method (WPM) and PCA. The total number of known COVID-19 patients in Bangladesh was 122,709 as of 24th June. Radical growth will be found with 4912 cases in one day on 16th July as per the time-series forecasting. The infection rate among the young (60) had the maximum death rate (≈39%). Both of India and Bangladesh, approximately one-third of total COVID-19 cases belong to the under 30 age group. Preliminary observation finds India and Bangladesh have a high risk for young people and the working class. PCA indicates the highest positive association among the youths and the highest negative association among the older. In this study, older age (>60) individuals are in danger with the fifth rank, and the young and working-age people are at comparatively lower risk with a third to the fourth rank in terms of infection rate as indicated by MCDM. 41-50 age group remains at lower risk with the first rank in all cases. The nature of activities of younger people and the poor immunity system of older people are the reason for the non-homogenous attitude toward the coronavirus among different age groups. In Bangladesh, drug addiction, gambling habits, uncontrolled lifestyle, and social obliquity have led the youth through danger, threatening the older age of family and society.
Keywords: COVID-19, Age-group, Transmission, Youngsters, Older-age, Immunity, Risk analysis, Bangladesh